Telegram-Based Earthquake Early Warning - Siregar, Arfanda Anugrah (International Journal of Artificial Intelligence Research, 2024)
Earthquakes are one of the natural disasters whose arrival cannot be ascertained and have a very detrimental impact, both in terms of property losses and lives. Indonesia, with its very active tectonic plate conditions, often experiences earthquakes, so it needs an effective early warning system. BMKG has developed an early warning system that informs of earthquake events through various media. However, this system still has weaknesses in the speed of delivering information to the public. This research aims to design and make a prototype of an earthquake early warning tool that can send information in the form of notifications and warning alarms using the Telegram application. The use of Telegram as a medium for conveying information was chosen because of its high speed, security, and accessibility. This research was carried out at the Medan State Polytechnic using the MPU 6050 sensor to detect earthquake vibrations and send data to a database containing seismic information. The results of the research were able to make a prototype of an earthquake early warning tool that uses Telegram for the dissemination of warning information in real-time, so that people can more quickly take self-rescue actions. The integration of Telegram in the earthquake early warning system is expected to increase the effectiveness of information dissemination and can be a faster and more efficient solution in dealing with earthquake disasters in Indonesia